LncRNA TCONS_00023297 Regulates the Balance of Osteogenic and Adipogenic Differentiation in Bone Marrow Mesenchymal Stem Cells and the Coupling Process of Osteogenesis and Angiogenesis - Wang, Haitao; Wei, Peng; Zhang, Yi; Li, Yuebai; Yin, Li (Frontiers in Cell and Developmental Biology, 2021)
Long noncoding RNA (lncRNA) is a noncoding RNA with a length of more than 200 bases. It plays an important role in the occurrence and development of diseases. Research on lncRNAs has received increasing attention. Bone is an important organ of the human body. As the population ages, the incidence of osteoporosis gradually increases. The mechanism of action of lncRNAs in the development of osteoporosis is unclear. The imbalance between osteogenic and adipogenic differentiation in bone marrow mesenchymal stem cells (hBMSCs) and the coupling process of osteogenesis and angiogenesis plays an important role in the development of osteoporosis. Therefore, this study focused on the mechanism by which lncRNAs regulate the osteogenic differentiation of bone marrow mesenchymal stem cells and the mechanism of action of lncRNAs in bone metabolism. The expression of lncRNAs in the osteogenic differentiation of hBMSCs was detected by lncRNA microarray. Real-time quantitative PCR was used to detect the expression changes of lncRNA and osteogenic genes during hBMSC osteogenic and adipogenic differentiation. The ceRNA mechanisms were detected by RIP and luciferase reporter gene assays. The effect of lncRNAs on the osteogenesis-angiogenesis coupling process was detected by Transwell assays. TCONS_00023297 increased expression during osteogenic differentiation; TCONS_00023297 overexpression promoted osteogenic differentiation of hBMSCs; BMP2 regulated TCONS_00023297 expression in a concentration- and time-dependent manner; TCONS_00023297 regulated miR-608 via a ceRNA mechanism; TCONS_00023297 inhibited hBMSC adipogenic differentiation; and TCONS_00023297 promoted VEGF secretion by hBMSCs. TCONS_00023297 regulates osteogenic differentiation, adipogenic differentiation and osteogenic-angiogenic coupling of hBMSCs via the TCONS_00023297/miR-608/RUNX2/SHH signaling axis.